Follow-up Care for Survivors of Prostate Cancer – Clinical Management: a Program in Evidence-Based Care Systematic Review and Clinical Practice Guideline. Issue 11 (November 2017) - Loblaw, A.; Souter, L.H.; Canil, C.; Breau, R.H.; Haider, M.; Jamnicky, L.; Morash, R.; Surchin, M.; Matthew, A.
Abstract: Aims: This clinical practice guideline was developed to provide evidence-based guidance on the frequency by which prostate-specific antigen (PSA) levels should be tested in men after curative-intent treatment for prostate cancer and to define the most appropriate diagnostic testing if biochemical recurrence occurs. Materials and methods: An electronic search using OVID was used to systematically search the MEDLINE and EMBASE databases for systematic reviews and primary literature. A systematic review and practice guideline was written, reviewed and approved by the Guideline Development Group (GDG) and Program in Evidence-Based Care Report Approval Panel. External review by three prostate experts was completed, as well as an online consultation with healthcare professionals who were intended users of the guideline. Results: Three systematic reviews and seven primary studies were included in the evidence base. All identified literature reported on diagnostic imaging properties of diagnostic tests following biochemical recurrence. Conclusions: Due to a lack of empirical research, few evidenced-based recommendations could be made with respect to a follow-up schedule of PSA testing for prostate cancer survivors following curative-intent treatment, or detailing diagnostic testing upon detection of biochemical recurrence. Accordingly, the GDG focused substantial effort on critical examination of the identified evidence, existing clinical practice guidelines and on obtaining clinical expertise consensus using a modified Delphi method. Overall, the recommendations embedded in this guideline reflect the best practice to date for the efficient and effective clinical follow-up care of prostate cancer survivors. Highlights: A practice guideline for follow-up care of prostate cancer survivors is summarized. Three systematic reviews and seven primary studies identified. Due to lack of published data, few evidence-based recommendations could be made. Critically examined evidence, existing guidelines and obtained clinical expertise. Recommendations provide best practice to date for clinical follow-up care.